Девушка с татуировкой дракона: [роман] / Стиг Ларссон - Ларссон Стиг (Millennium, 2010)
Экземпляры: ф.18 (20221223) / Инвентарный номер: 4253 / Цена: / Сис.шифр: 84(4Шве)-4 / Авт.знак: Л 25 / ГРНТИ: 17.82.31 / ББК: 84(4Шве)-44